The Queen of Sheba : a colonial icon - Nel, Philip Johannes (Journal for semitics, 2004)
This paper takes its cue from the critical framework of postcolonial discourse analysis, which is applied in this instance to the novel Di Koningin fan Skeba by S J du Toit (1898). Specifically, this article focuses on the narrative trope or icon of the Queen of Sheba as a signifier of a colonial desire to dehistoricize or displace the African indigenous space with a coherent picture that would maintain and manifest the megastory of the coloniser. The Queen of Sheba becomes the icon of colonised heroism that reinstates the connection to the prehistory and religion of the coloniser. The text under discussion dates from the colonial period of South Africa. At the time, the independent republics were at loggerheads with the imperial aspirations of Great Britain, and debates about the political accommodation of the indigenous nations were the order of the day. This colonial text, however, totally silenced or devoiced the indigenous people and objectified them as "Other", in line with the hegemony of colonial superiority. The text is also a perfect example of the manner in which colonial discourses were intertwined with religion.